Behavioral Counseling Model With Relaxation Techniques To Minimize Learning Anxiety - Chitra Charisma Islami; Dwi Sri Rahayu; Nika Cahyati (Universitas Muhammadiyah Kuningan, 2021)
This research has been aimed at (1) depicting the realization of individual counseling, (2) depicting students’ anxiety in facing Arabic Language lesson, (3) finding behavioral counseling model to minimize anxiety of the students facing the lesson of Arabic Language, (4) finding out the effectiveness of behavioral counseling model by means of relaxation technique in SMAN (state-run senior high schools) of Majalengka Regency of the Province of West Java. This research is of research and development (RnD) model with the following features: (1) introduction, (2) formulation of the hypothetic model, (3) feasibility test on the hypothetic model, (4) enhancement of the hypothetic model, (5) limited trials, and (6) results on end products. Sampling of this research applies a purposive sampling technique. The number of students who become the sample in this research is 6 students. This research answers four problem formulations; i.e. (1) behavioral counseling with relaxation technique has not been implemented because BK teachers do not have a proper model concerning the realization of the procedures, (2) the anxiety levels before the treatment is given are categorized high, (3) the behavioral counseling model with relaxation technique proves to be effective to minimize anxiety of the students in facing Arabic Language lesson in SMAN (state-run senior high schools) of Majalengka Regency with Wilcoxon’s statistic test resulting in 0.028 < 0,05 and showing a decrease in pretest and posttest amounting to 47.83 points.